1997
DOI: 10.1073/pnas.94.23.12497
|View full text |Cite
|
Sign up to set email alerts
|

The absence of effect of gid or mioC transcription on the initiation of chromosomal replication in Escherichia coli

Abstract: Despite the widely accepted view that transcription of gid and mioC is required for efficient initiation of cloned oriC, we show that these transcriptions have very little effect on initiation of chromosome replication at wild-type chromosomal oriC. Furthermore, neither gid nor mioC transcription is required in cells deficient in the histone-like proteins Fis or IHF. However, oriC that is sufficiently impaired for initiation by deletion of DnaA box R4 requires transcription of at least one of these genes. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 38 publications
1
52
0
1
Order By: Relevance
“…The proposed mechanisms by which transcription from mioC could inhibit replication were that transcription could impair formation of initiation complex at the origin via physical interactions which would displace DnaA from DNA or through the generation of local changes in the DNA topology destabilizing the initiation complex. However, while the replication time in cells lacking mioC promoter was unaffected (Bates et al 1997;Lobner-Olesen et al 1992), transcription from this promoter became essential for cell viability when the dnaA box R4 was deleted suggesting a positive role for mioC transcription in replication initiation (Bates et al 1997). Despite of all the data obtained over 3 decades, no clear consensus on the role of transcription from the mioC gene on replication has been achieved.…”
Section: Transcription Of Mioc and Its Effect On Replication Initiationmentioning
confidence: 89%
“…The proposed mechanisms by which transcription from mioC could inhibit replication were that transcription could impair formation of initiation complex at the origin via physical interactions which would displace DnaA from DNA or through the generation of local changes in the DNA topology destabilizing the initiation complex. However, while the replication time in cells lacking mioC promoter was unaffected (Bates et al 1997;Lobner-Olesen et al 1992), transcription from this promoter became essential for cell viability when the dnaA box R4 was deleted suggesting a positive role for mioC transcription in replication initiation (Bates et al 1997). Despite of all the data obtained over 3 decades, no clear consensus on the role of transcription from the mioC gene on replication has been achieved.…”
Section: Transcription Of Mioc and Its Effect On Replication Initiationmentioning
confidence: 89%
“…The mioC gene is located next to oriC on the E. coli chromosome and although several investigations have tried to establish a role for mioC transcription in chromosome replication (22)(23)(24), the results were inconclusive (25,26 (7); lane 5, assay containing all standard components plus fraction 25 from the final Mono Q column (see Fig. 2) .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of DNA replication by transcription has been found in both prokaryotic (3,11,35,56,70) and eukaryotic (48, 60) cells. On the other hand, transcription has been found to suppress replication in bacterial plasmid DNA (47, 53) and in yeast (77, 82), tetrahymena (61), and human (33) cells.…”
mentioning
confidence: 99%
“…The CMV enhancer was also found to exhibit an inhibitory effect on the CMV enhancer-promoter driving chloramphenicol acetyltransferase expression in a dose-dependent manner. Together these results suggest that inhibition of SV40 origin-based DNA replication by the CMV enhancer is due to intramolecular competition for the formation of active chromatin structure.A majority of DNA replication origins in both prokaryotic (3,11,35,42,53,56,59) and eukaryotic (1, 5, 12, 17-19, 24, 25, 36, 38, 41, 43, 48, 60, 62-66, 68, 71, 75, 78, 81, 83, 84, 93-95) cells are closely associated with a transcription unit. Recent characterization of origins of replication in mammalian cells has shown that the origins are located very close to a transcription unit or even within a transcription unit (see review in reference 20).…”
mentioning
confidence: 99%
See 1 more Smart Citation